A construção do Rio De Janeiro na literatura de viagem oitocentista - Gagliardo, Vinícius Craneck (Universidade Federal de São Paulo - UNIFESP, 2016)
Abstract: This paper aims to map the construction of the Rio de Janeiro in the nineteenth century travel literature. Starting by the analysis of what are the travel accounts and how such descriptions allow the formulation of a certain idea of Brazil that began to circulate in the Atlantic World, I intend to scan which image of the Rio de Janeiro was built in the narratives of those foreigners. For this, I tried to leave the quotes speak for themselves, other words, I tried to restore the voice to these individuals, with the expectation to rebuild - even partially - and question what foreign travelers, after all, had to say about the events that they were involved.

Resumo: Este artigo tem por objetivo mapear a construção do Rio de Janeiro na literatura de viagem oitocentista. Partindo da análise sobre o que são os relatos de viagem e como tais descrições permitiram a formulação de uma certa ideia de Brasil que passou a circular no Mundo Atlântico, pretendo esquadrinhar que imagem do Rio de Janeiro foi construída nas narrativas desses estrangeiros. Para isso, procurei deixar as citações falarem por si próprias, ou seja, procurei restituir a voz a estes indivíduos, com a expectativa de reconstituir - ainda que parcialmente - e interrogar o que os viajantes estrangeiros, afinal, tinham a dizer sobre os acontecimentos em que estavam envolvidos.
The construction of the Rio De Janeiro in the nineteenth century travel literature
Keywords: literatura de viagem; Rio de Janeiro; século XIX; literatura de viagem; Rio de Janeiro; século XIX